Modelling the coach-athlete relationship (CAR) on specific motor tasks and team performance - Palmizal,; Indrayana, Boy; Putra, Anggrawan Janur; Murniati, Sri; Setiawan, Edi (Journal Sport Area, 2026)
Background: Motor tasks (MT) and team performance (TP) are important aspects for young basketball athletes. However, empirical evidence examining the mediating role of specific motor tasks in the relationship between coach–athlete relationships and team performance among youth basketball athletes remains limited. Objectives: Thus, our current study aims to investigate how CAR is related to MT and TP and how MT mediates TP. Methods: Our current study employed a cross-sectional design. We also recruited 180 young basketball players. The Coach-Athlete Relationship Questionnaire (CAR) was used to measure performance. This study employed Structural Equation Modelling (SEM) analysis. Results: We observed that CAR was significantly related to MT (β = 0.68, p < 0.001) and TP (β = 0.45, p < 0.001). In addition, we observed that MT mediated the effect directly with TP (β = 0.52, p < 0.001). Conclusion: We conclude in our findings that the quality of MT and TP is greatly influenced by CAR. Therefore, it is important for coaches to start focusing on the development of CAR in young basketball athletes. Therefore, this study contributes to the literature on how TP is significantly related to CAR and MT. Furthermore, the findings of this study provides valuable information for basketball coaches about the importance of CAR and MT for future athlete performance.